An Analysis of Overstory Tree Canopy Cover in Sites Occupied by Native and Introduced Cottontails in the Northeastern United States with Recommendations for Habitat Management for New England Cottontail - Buffum, Bill (PLoS One, 2015)
The New England cottontail (Sylvilagus transitionalis) is a high conservation priority in the Northeastern United States and has been listed as a candidate species under the Endangered Species Act. Loss of early successional habitat is the most common explanation for the decline of the species, which is considered to require habitat with dense low vegetation and limited overstory tree canopy. Federal and state wildlife agencies actively encourage landowners to create this habitat type by clearcutting blocks of forest. However, there are recent indications that the species also occupies sites with moderate overstory tree canopy cover. This is important because many landowners have negative views about clearcutting and are more willing to adopt silvicultural approaches that retain some overstory trees. Furthermore, it is possible that clearcuts with no overstory canopy cover may attract the eastern cottontail (S. floridanus), an introduced species with an expanding range. The objective of our study was to provide guidance for future efforts to create habitat that would be more favorable for New England cottontail than eastern cottontail in areas where the two species are sympatric. We analyzed canopy cover at 336 cottontail locations in five states using maximum entropy modelling and other statistical methods. We found that New England cottontail occupied sites with a mean overstory tree canopy cover of 58% (SE±1.36), and was less likely than eastern cottontail to occupy sites with lower overstory canopy cover and more likely to occupy sites with higher overstory canopy cover. Our findings suggest that silvicultural approaches that retain some overstory canopy cover may be appropriate for creating habitat for New England cottontail. We believe that our results will help inform critical management decisions for the conservation of New England cottontail, and that our methodology can be applied to analyses of habitat use of other critical wildlife species.